Schizophrenia: a Look from Science, Technology and Society - Dinorah Janet Torres Lugo; Iván Castillo Ledo; Iriam Rojas Díaz; Antonio Masot Rangel; Silvia Janet Masot Torres; Ana Esther Cabrera Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Schizophrenia is probably the most enigmatic and tragic disorder that psychiatrists treat, and perhaps the most devastating. It manifests itself in youth, so schizophrenic patients usually live many years after the onset of the disease and continue to suffer from its effects without being able to lead a completely normal life. A bibliographic review was carried out using the resources available in Infomed, specifically in the EBSCO and SCIELO databases and textbooks by Cuban and foreign authors. The analytical-synthetic method was applied and 18 scientific articles were reviewed. The elements that address the historical-cultural development of schizophrenia from the perspective of science, technology and society were exposed. This review was carried out with the aim of contributing to the knowledge about the historical cultural development of schizophrenia, taking into account the theories that man has developed through science to explain the appearance of the disease and the importance of social factors in the appearance, evolution and rehabilitation of this condition.